Rationale and design of feeding America's bravest: Mediterranean diet-based intervention to change firefighters' eating habits and improve cardiovascular risk profiles - Sotos-Prieto, Mercedes; Cash, Sean B.; Christophi, Costas A.; Folta, Sara C.; Moffatt, Steven M.; Muegge, Carolyn M.; Korre, Maria; Mozaffarian, Dariush; Kales, Stefanos N. (My University, 2017)
Among US firefighters, cardiovascular disease is the leading cause of on-duty death. Poor diet contributes to this burden, but effective strategies to encourage healthy eating in the fire service are not established. “Feeding America's Bravest” motivates firefighters and their families to modify their food culture and reduce cardiometabolic risk profiles by adopting Mediterranean diet principles. Feeding America's Bravest is a cluster-randomized, controlled trial within the 44 stations of the Indianapolis Fire Department, including about 1000 firefighters. It compares a Mediterranean Diet Nutritional Intervention (group 1) vs. usual care (group 2) for 12 months; followed by 12 months of self-sustained continuation phase in the group 1 and cross-over to Mediterranean Diet Nutritional Intervention in group 2. Group 2 will receive the MDNI for 6 months to test the efficacy of a shorter intervention followed by 6 months of self-sustained phase. The intervention includes behavioral and environmental components. The primary outcome is 12-month change in Mediterranean diet score comparing group 1 vs. group 2; we will also assess 12- and 24-month change in group 1, and 6- and 12-month change in group 2, from baseline. Secondary outcomes are changes in body weight, body composition and other cardiometabolic risk markers; and correlations between self-reported dietary habits and biomarkers of dietary adherence. This innovative trial tests a novel worksite approach to introduce Mediterranean diet among US firefighters, informing recommendations for the US fire service and potentially other similar workforces.
Keywords: Firefighters; Mediterranean diet; Randomized control trial; Workplace